If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-2x + -2) * 3 = 0 Reorder the terms: (-2 + -2x) * 3 = 0 Reorder the terms for easier multiplication: 3(-2 + -2x) = 0 (-2 * 3 + -2x * 3) = 0 (-6 + -6x) = 0 Solving -6 + -6x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -6x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -6x = 0 + 6 -6x = 0 + 6 Combine like terms: 0 + 6 = 6 -6x = 6 Divide each side by '-6'. x = -1 Simplifying x = -1
| 3x-12+2x+10=180 | | 3/8*72 | | -7(3p+4)-14=3(4p+8) | | 4x-y-z=7 | | y=1/z=3 | | 2=7-3x | | 67/7 | | 45mi/h= | | Z/3-8-4 | | -5(-4/15) | | -x-8y+2=10 | | 5x-5(-4/15)=4 | | 7/3x-2=12 | | y=1.75x+1 | | -6+-3+-9-(-2)= | | r-1.8=9 | | 50/15 | | 5t^2+t-42=0 | | e^12+e^6=0 | | -8x=9x | | 8x+4=4x-12(x-1) | | 10y^2-41y+40=0 | | 144=b^2-12b | | 8n+56= | | 6/7÷3/28 | | 5xa-18-4a=-36 | | 5*a-18-4a=-36 | | 71=5(3k-8)-2(3k+2) | | 3(-4)6-2(6)(-9)-72+108= | | 3(-4)6-2(6)(-9)(-72)+108= | | 2x+8x-1=14+5x | | 24x+15=6x+17 |